دور المراكز العلمية بالجنوب التونسي في الحفاظ على الهوية العربية والإسلامية لمنطقة وادي سوف - قدع, محمد العيد (University of Eloued جامعة الوادي, 2022)
تتناول هذه الدراسة؛ أهم رافد للحياة العلمية بوادي سوف أثناء فترة الاحتلال الفرنسي، وهي المراكز العلمية بالجنوب التونسي، وأهمها الزوايا وفروع الزيتونة بجنوب تونس، التي كان الطلبة السوافة يشدّون إليها الرحال نهلا للعلم وتوقا للمعرفة، وقد أبرزنا أمثلة من طلبة العلم من أهل سوف الذين كوّنوا أشبه بالبعثات العلمية الحرة نحو الجنوب التونسي، وبعد تخرج هؤلاء الطلبة وعودة أغلبهم إلى ديارهم، كان لهم تأثير بارز، في تولي مهمة تعليم أبناء المنطقة من طلاب العلم، ولم ينحصر دورهم في ميدان العلم، بل لهم دور جليل في ميدان الإصلاح، والوقوف سدّا منيعا أمام المخططات الاستعمارية الرامية للقضاء على الدين الإسلامي، ومحاربة اللغة العربية، وبالتالي كان من أبرز الأعمال الجليلة لأبناء سوف المهاجرين لمنطقة الجنوب التونسي قصد طلب العلم، هو الحفاظ على الهوية العربية والإسلامية للمنطقة. كما يبين هذا البحث بوضوح؛ حركة الهجرة المستمرة والحثيثة بين منطقتي وادي سوف والجنوب التونسي، ومتانة الأواصر بين المنطقتين، وكيف كان طلبة سوف حلقة وثيقة تربط منطقتهم والبلاد التونسية خاصة جنوبها Abstract : This study deals with; The most important tributary to scientific life in Oued Souf during the period of the French occupation, which are the scientific centers in southern Tunisia, the most important of which are the corners and the Zaytuna branches in southern Tunisia, to which the Swafa students used to travel for knowledge and a yearning for knowledge. Al Hurra towards the south of Tunisia, and after the graduation of these students and the return of most of them to their homes, they had a prominent influence in assuming the task of educating the people of the region from the students of knowledge, and their role was not limited to the field of science, but rather they had a great role in the field of reform, and standing as an impenetrable barrier against colonial plans Aiming to eradicate the Islamic religion, and to fight the Arabic language, and thus one of the most prominent works of the sons of Souf who immigrated to the southern Tunisian region in order to seek knowledge, is to preserve the Arab and Islamic identity of the region. As this research clearly shows; The continuous and intense migration movement between the regions of Oued Souf and southern Tunisia, the strength of the bonds between the two regions, and how the students of Souf were a close link linking their region and Tunisia, especially its south.
The role of scientific centers in southern Tunisia In preserving the Arab and Islamic identity of the Oued Souf region
مداخلة
Keywords: وادي سوف؛ الجنوب التونسي؛ التعليم العربي الإسلامي؛ البعثات العلمية؛ حركة الإصلاح; Oued Souf; southern Tunisia; Arab Islamic education; scientific missions; reform movement